2021
DOI: 10.1109/access.2021.3099973
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Classification Accuracy of Transhumeral Prosthesis: A Hybrid sEMG and fNIRS Approach

Abstract: Limited non-invasive transhumeral prosthesis control exists due to the absence of signal sources on amputee residual muscles. This paper introduces a hybrid brain-machine interface (hBMI) that integrates surface electromyography (sEMG) and functional near-infrared spectroscopy (fNIRS) signals to overcome the limits of existing myoelectric upper-limb prosthesis. This hybridization aims to improve classification accuracy (CA) to escalate arm movements' control performance for individuals who have transhumeral am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…The initial search yielded 108 articles. Once the duplicates were removed and eligibility criteria were applied, 10 articles with a total of 180 participants were included in the review [ 4 , 7 , 9 , 10 , 11 , 18 , 19 , 20 , 21 , 22 ]. The characteristics of included studies are shown in Table 2 and Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial search yielded 108 articles. Once the duplicates were removed and eligibility criteria were applied, 10 articles with a total of 180 participants were included in the review [ 4 , 7 , 9 , 10 , 11 , 18 , 19 , 20 , 21 , 22 ]. The characteristics of included studies are shown in Table 2 and Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…One study (n = 19) included a sample of children with cerebral palsy (CP) with ages ranging from 8 to 18 years [ 22 ]. Three studies (n = 7) included patients with upper limb amputation: one of them did not specify the amputation level [ 4 ], another included transradial amputees [ 19 ] and the other transhumeral amputees [ 20 ]. Five studies (n = 31) examined patients with stroke [ 7 , 9 , 11 , 18 , 21 ]: three of them did not specify the characteristics of the impairment, one included people (n = 3) with mildly to severely impaired hand function [ 11 ], and the other included people (n = 4) with different levels of impairment [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations